Can Small Farmers Protect Themselves Against Bad Weather? - World Bank (Washington, DC, 2015)
Severe weather conditions can undo even the best efforts of families to break free of poverty. Households that rely on subsistence or small-scale farming are especially at the mercy of severe weather. Droughts and floods wipe out crops, leaving families hungry or without anything to sell to pay for essentials such as school fees or medicines. Climate changes have made weather even more variable in many countries, exacerbating problems such as droughts, extreme temperatures and flooding. Policymakers seeking to offset the unexpected have increasingly used cash transfer programs to help families through difficult times. But what makes a difference in the long-term? Are small grants or training programs effective methods to help farm households develop non-agricultural businesses, thereby enabling them to better manage weather shocks? To understand what might allow families to better manage risks, the World Bank supported an evaluation of a pilot program in Nicaragua to encourage rural households to diversify beyond small-scale farming. The project found that two years after the program ended, households that received vocational training or investment grants to start non-agricultural businesses were better protected against the negative effects of severe drought than families that only received conditional cash transfers. These results suggest that helping farmers develop other income-generating different businesses can be an effective and sustainable approach to reducing poverty by protecting them against the financial repercussions of severe weather and climate changes. This Evidence to Policy note was jointly produced by the World Bank Group, the Strategic Impact Evaluation Fund (SIEF), and the British governments Department for International Development.